HOLISTIC LIFE STYLE AND FOOD HABITS FOR EFFECTIVE MANAGEMENT IN ARSHAS (HAEMORRHOIDS) - AN AYURVEDIC VIEW - KHODE, NAKUL; NAMBURI, SHILPA; NAMBURI, *SEKHAR; JADHAV, SHUBHANGI; SURYAWANSHI, MILIND (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda places great importance on ones pathya or lifestyle (eating habits and daily routine). Ayurveda provides us with the knowledge of how to prevent disease and how to eliminate its root cause if it occurs. Arshas (haemorrhoids/ piles) are common and unique disease to humans at some time in their life as no other living being suffers with this ailment. Further in the classics of Ayurveda explained that ailment kills the afflicted like an enemy hence it is coined as Arshas. The disease is initiated with Agnimandya (Improper digestion) due to improper food habits and lifestyles. Further Agnimandya leads chronic constipation and manifest the disease. In Ayurveda and contemporary medical science various conservative and surgical methods are described. However haemorrhoids can reoccur even after the good quality of the management hence in Ayurveda it is mentioned as one among Ashtamahagada (diseases difficult to treat). In this regard various reasons are explained for re-manifestation of the disease among those important factors is not maintaining the proper food habits and lifestyle methods. In these conditions Ayurveda is having major role as greater importance has been given in correction of the food habits and modification of the lifestyles as a main factor or acts as a adjuvant to the therapies in treating the diseases. In the management of Arshas various regimens of food habits and lifestyles are described. If these are implemented properly helps in increase appetite, reduces constipation and also prevents the manifestation as well as avoids recurrence of the disease.